Association of hospital and community factors on the attainment of Baby‐Friendly designation: A breastfeeding health promotion - Aurora Tafili; Nazik M. A. Zakari; Hanadi Y. Hamadi; Aaron Spaulding (Wiley, 2022)
Abstract The Baby‐Friendly Hospital Initiative is a global health promotion intervention that outlines the Ten Steps hospitals should implement to support newborns' breastfeeding. This US‐based study aimed to determine which hospital characteristics and community factors are associated with hospitals' attainment of Baby‐Friendly designation. We used a cross‐sectional design and used 2018 data from the Baby‐Friendly, USA Inc. designation program merged with the American Hospital Association annual survey data set. Multilevel logistic regression analysis was used to assess hospital characteristics of interest among the sample consisting of 312 Baby‐Friendly hospitals and 1449 non‐Baby‐Friendly. Our results show that Baby‐Friendly hospitals are more likely to be government nonfederal hospitals, in the Midwest or South regions, serve communities with higher birth totals, and reside in competitive markets. Based on the results of this study, hospitals should seek further and examine their community's characteristics and structures to identify opportunities and encourage the attainment of improved breastfeeding initiatives such as Baby‐Friendly designation.